An adaptive intelligent alarm system for wireless sensor network - Ayman Dawood Salman; Osamah Ibrahim Khalaf; Ghaida Muttasher Abdulsaheb (Institute of Advanced Engineering and Science, 2019)
Security is one of the imperative issues in an advanced local condition. The current center around formative and research issues of Wireless Sensor Network(WSN) based Smart Home. WSN based shrewd home detection system gives a safe and safe living condition. A Wireless Sensor System (WSN) is a system which is building by utilizing little independent hubs (sensors). Its motivation is to screen certain ecological parameters, for example, temperature, dampness, brilliance, weight, sound, movement, and so forth. This paper depicts the improvement of a smart home condition dependent on exact Wireless Sensor Network and furthermore depicts private vitality observing and controlling procedures for keen home systems administration framework. This paper proposes a basic and adaptable remote arrange for domestics computerization of temperature, moistness, gas, movement and light by executing dependable sensor hubs which can be controlled too observed. This innovation offers energizing and new chance to build the availability of devices inside the home for the home computing.